2020
DOI: 10.3389/fnins.2020.00210
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Two-Photon Imaging Reveals Acute Cerebral Vascular Spasm and Microthrombosis After Mild Traumatic Brain Injury in Mice

Abstract: Mild traumatic brain injury (mTBI), or concussion, is reported to interfere with cerebral blood flow and microcirculation in patients, but our current understanding is quite limited and the results are often controversial. Here we used longitudinal in vivo twophoton imaging to investigate dynamic changes in cerebral vessels and velocities of red blood cells (RBC) following mTBI. Closed-head mTBI induced using a controlled cortical impact device resulted in a significant reduction of dwell time in a Rotarod tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…For instance, histological evidence from human patients indicated that microvascular dysfunction widely occurred from mild to moderate and severe TBI, and not only in the acute and subacute stages after the primary injury but also in the chronic stage in long-term survivors ( O’Keeffe et al, 2020 ). These clinical findings are in general backed up by the evidence from preclinical animal models ( Sandsmark et al, 2019 ), which demonstrated that mTBI induces cellular and molecular events at the BBB, including alteration of endothelial transport functions ( Villalba et al, 2017 ), disruption of the crosstalk between endothelial cells and pericytes ( Bhowmick et al, 2019 ), pericyte loss ( Zehendner et al, 2015 ), cerebral blood flow (CBF) reduction, and tissue hypoxia ( Han et al, 2020 ; O’Keeffe et al, 2020 ). These vascular pathological events interact and evolve with neuroinflammation ( Blennow et al, 2012 ) and contribute to chronic neurodegeneration post-injury.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, histological evidence from human patients indicated that microvascular dysfunction widely occurred from mild to moderate and severe TBI, and not only in the acute and subacute stages after the primary injury but also in the chronic stage in long-term survivors ( O’Keeffe et al, 2020 ). These clinical findings are in general backed up by the evidence from preclinical animal models ( Sandsmark et al, 2019 ), which demonstrated that mTBI induces cellular and molecular events at the BBB, including alteration of endothelial transport functions ( Villalba et al, 2017 ), disruption of the crosstalk between endothelial cells and pericytes ( Bhowmick et al, 2019 ), pericyte loss ( Zehendner et al, 2015 ), cerebral blood flow (CBF) reduction, and tissue hypoxia ( Han et al, 2020 ; O’Keeffe et al, 2020 ). These vascular pathological events interact and evolve with neuroinflammation ( Blennow et al, 2012 ) and contribute to chronic neurodegeneration post-injury.…”
Section: Introductionmentioning
confidence: 99%
“…Because gliovascular and neurovascular interactions control cerebral blood flow at multiple levels, their disruption following blast exposure would be expected to affect cerebral autoregulation. Morphological, biochemical and functional studies of humans and animal models have identified the vasculature as a primary target for blast-induced tissue damage [ 2 , 6 , 32 , 38 41 , 45 , 50 , 54 , 63 , 66 , 75 , 82 , 112 114 , 116 , 130 133 , 138 ]. Considerable evidence supports the concept of a thoracic effect whereby pressure waves transmitted through the systemic circulation damage the brain providing an additional mechanism for why blood vessels and perivascular cellular elements may be particularly susceptible to blast injury [ 116 , 117 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of mTBI model: mTBI was created using a technique described recently 16,17 . Before injury, mice were anesthetized with a mixture of ketamine (87.7 mg/mL) and xylazine (12.3 mg/mL) and placed in a stereotaxic frame.…”
Section: Animalsmentioning
confidence: 99%